OPTIMIZATION OF ROAD SAFETY PARTNERSHIP ACTION (RSPA) IN HANDLING TRAFFIC PROBLEMS IN THE JURISDICTION OF THE TANJUNG PRIOK PORT POLICE STATION - Yunita Natallia Rungkat; Chairul Muriman Setyabudi; Basir S. (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The Tanjung Priok Port in Indonesia faces challenges in traffic management and road safety. To address these issues, the Tanjung Priok Port Police Traffic Unit has implemented Road Safety Partnership Action (RSPA) activities. This study aims to determine the implementation of Road Safety Partnership Action (RSPA) activities carried out by the Tanjung Priok Port Police Traffic Unit in handling traffic problems in the Tanjung Priok Port area. The study incorporates various theories, including Rosen's cooperation theory, Terry's management theory (including planning, organizing, implementing, and supervising), Dr. E Mulyana's competency theory, and problem-solving theory. A qualitative approach with descriptive analysis was employed. The findings revealed suboptimal implementation of the RSPA activities by the Tanjung Priok Port Police Traffic Unit in addressing traffic and road transportation issues. Furthermore, the competence of the Satlantas Polres Pelabuhan Tanjung Priok personnel in executing the RSPA activities was also deemed suboptimal. The active system and methodology employed in the RSPA activities have not been fully maximized. Therefore, optimization measures are required, including strengthening coordination and communication capabilities, empowering budget support and improving facilities and infrastructure in RSPA activities, enhancing the enforcement of traffic violations and management of traffic accidents, fostering personnel quality in executing the RSPA activities, implementing traffic engineering measures in anticipation of increased port activities related to transportation, encouraging community participation, and utilizing advancements in information technology, particularly in traffic engineering within the Tanjung Priok Port area.